A sustainable approach to replace bleed stream in electrical refining of copper - Mohammadreza Shojaei; Gholamreza Khayati; Mohammadjavad Korasani (Materials Letters: X, 2022)
Despite extensive studies on electrorefining to remove impurities from copper production units, bleeding electrolytes is the most popular method for controlling impurities due to low operating costs. A controlled cooled-reheat cycle was used to remove impurities in industrial electrolytes of Khatoon Abad copper company. Phase identification and physical study were done by the XRD, SEM, TEM, and FTIR techniques. The results confirmed the possibility of the removal of 23 wt% Ni, 26 wt% Sb, 2.4 wt% As and convention of 6 wt% of As5+ to As3+ at cooled-reheat cycle.